The Influence of Financial Literacy, Financial Attitudes, and Self-Efficacy on Housewives Financial Management - Priscilla, Ananda; Widiastuti, Anna (SMARTINDO, 2024)
Purpose - This research aims to test and analyze the influence of financial literacy, financial attitudes, and self-efficacy on financial management. Apart from that, this research aims to obtain empirical evidence of the influence of financial literacy, financial attitudes and self-efficacy on financial management. Design/methodology/approach - This research is included in the type of quantitative research. The population used in this research were housewives in Panggang Village, Jepara Regency. The sampling method in this research is the census method. The number of samples obtained was 150. In obtaining the information needed in this research, the researchers carried out observations, distributed questionnaires and also interviews. This research uses the outer model and inner model methods with the help of SmartPls. Findings and Discussion - The results of this research show that financial literacy, financial attitudes, and self-efficacy have a significant effect on financial management. From all the independent variables that have been studied, it can be seen that financial attitudes have the most dominant influence on financial management compared to the other two variables. This is proven by the results in the diagram which show that a large percentage is occupied by the financial attitude variable. Conclusion - Overall, research shows that increasing financial literacy, positive financial attitudes, and self-efficacy can positively influence housewives' financial management. Therefore, it is important to develop financial education programs that not only increase knowledge, but also build attitudes and beliefs that support better financial management among housewives.